Genetic parameters of fertility traits of cows milked once daily versus twice daily in New Zealand : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Animal Science at Massey University, Manawatū, New Zealand - Jayawardana, Jayawardana Mudiyanselage Dinesha Rajinee (Massey University, 2023)
In New Zealand about 55% of dairy herds are milked twice daily (TAD) and about 9% of herds are milked once daily (OAD) for their entire lactation, with the balance of herds using variable milking frequencies across the lactation. The general aim of this thesis was to estimate genetic parameters for fertility traits of spring-calved OAD and TAD milking cows in New Zealand. Cows milked OAD for the entire lactation were more fertile than cows milked TAD for the entire lactation. Heritability and repeatability estimates for milk production and fertility traits were broadly consistent for cows that were milked either OAD or TAD for their entire lactation. Though genetic correlations between milk production and fertility were antagonistic in both milking systems, correlations between milk production and the key reproductive metrics of 6 wk in-calf, not in-calf rate and 6 wk calving were less strong in cows milked OAD compared with TAD. In both OAD and TAD milking populations, individual breed effects for milk, fat, protein and lactose yields were in favor of Friesian (F) cows; however, maternal breed effects for yields were in favor of Jersey (J) dams. Jersey cows were more fertile than the F cows in both milking populations, but maternal breed effects for fertility traits were in favour of F dams. Favourable F×J heterosis for milk production and fertility traits were significant in both milking cow populations. Recombination loss effects were sometimes favorable for production and fertility traits, but most estimates were small with larger standard errors. A genome-wide association study (GWAS) was conducted using 1,537 spring-calved dairy cows genotyped with Bovine Illumina 50K single nucleotide polymorphisms (SNPs) chips in two Massey University dairy herds. Four SNPs on chromosome 14 were highly significant for fat and protein percentages and associated genes were DGAT1, SLC52A2, CPSF1 and MROH1. The GWAS identified 10 candidate genes (KCNH5, HS6ST3, GLS, ENSBTAG00000051479, STAT1, STAT4, GPD2, SH3PXD2A, EVA1C and ARMH3) associated with fertility traits, which relate to functions, reduced metabolic stress and increased insulin secretion during the mating period, early embryonic development, fetal growth, and maternal lipid metabolism during the pregnancy period. Overall, the results of this thesis indicate milking OAD for the entire lactation improves the fertility performance of dairy cows but reduces milk production. The antagonistic genetic correlations between milk yield and key fertility measures were weaker in the OAD milking population than in the TAD milking population. The findings of this thesis can be used to develop a selection index for production and fertility traits in OAD milking cow population in New Zealand.
Keywords: Dairy cattle; Fertility; Genetics; Milking; Milk yield; New Zealand; Dean's List of Exceptional Theses; 300305 Animal reproduction and breeding